Barriers to Bystander Intervention in Sexual Harassment: The Dark Triad and Rape Myth acceptance in Indonesia, Singapore, and United Kingdom - Lyons, Minna (Journal of interpersonal violence, 2022)
Bystanders have an important role in preventing sexual violence, but they are often reluctant to intervene due to a range of barriers. In this study, we investigated relationships between the Dark Triad of personality (i.e. psychopathy, Machiavellianism and narcissism), rape myth acceptance and five bystander barriers. We addressed the paucity of research by collecting data from three countries (Indonesia, Singapore, and United Kingdom). In total, 716 University staff and students participated in an online survey. We found very few country-level differences in the correlations between the variables. In regression analyses, Machiavellianism and rape myth acceptance both had significant, positive relationships with failure to identify risk, failure to take responsibility, skills deficits and audience inhibition. Narcissism and psychopathy were significantly, negatively associated with audience inhibition and skills deficits. Findings indicate similarity in predictors of perceived barriers to bystander intervention across the three countries.